PEMBERIAN EDUKASI TENTANG GOOD MENSTRUAL HYGIENE PRACTICE PADA KEGIATAN POSYANDU REMAJA ANGGUN NAN TONGGA DI KOTA PARIAMAN - Yessy Markolinda; Mery Ramadani; Trisfa Augia (BULETIN ILMIAH NAGARI MEMBANGUN, 2023)
Based on data released by UNICEF in 2020, it was found that 1 in 5 girls in Indonesia do not know about hygiene management during menstruation. Taboos and stigma limit female students' activities during menstruation. The absence of female students at school makes them miss out on their lessons. Menstrual Hygiene Management (MKM) is the management of hygiene and health for women who menstruate. The Ministry of Health strives for menstrual hygiene by implementing three School Health Efforts (Trias UKS), namely health education, health services and fostering a healthy school environment. The aim of this activity is to provide education to teenagers regarding personal hygiene practices during menstruation. The activity was carried out at the Anggun Nan Tongga Youth Posyandu which is included in the work area of ​​the Pauh Community Health Center, Kampung Jawa I, Kota Pariaman and was held on August 19 2021 at the Village Head Office. Java I. The number of participants who attended were 20 teenagers at elementary, middle and high school levels who were active in Youth Posyandu activities. Education is delivered using lecture and discussion methods, and is equipped with supporting media in the form of slides and leaflets. The evaluation used is a pretest and post-test to determine whether there is an increase in teenagers' knowledge. After being given education, it was found that 65% of teenagers already had a high level of knowledge regarding hygiene management during menstruation. Teenagers already have good knowledge about how to manage hygiene during menstruation and also understand how to dispose of used sanitary napkins.